A Review Article on the Role of Arshoghna Mahakashaya in the Sushka Arsha Treatment. - kumari, Radha; mittal, Ashok; Singh, Chandan; Adlakha, Manoj Kumar; Purvia, Rajendra Prasad (International Research Journal of Ayurveda & Yoga, 2024)
Several treatises compiled throughout ancient times provide distinct modalities and drugs in the Ayurvedic traditional text. Drugs are crucial therapeutically because they are responsible for the overall balance of the body. The first division of the Charak Samhitha, known as Sutrasthan or shloksthan, is divided into eight parts. The medications are discussed in four chapters known as Bheshajachatushka or Aushadhachatushka in the sutrasthan. The medications are categorized here based on their pharmacological and pharmacotherapeutic properties. Mahakashaya is a classification system for medications based on Karmas, which is divided into fifty divisions. Arshoghan Mahakashaya is the twelfth category of medicines thought to be useful in the treatment of piles. Sushka arsha is a condition in which a person’s life is made unbearable by pain and swelling of the pile mass, with bheshaj chikitsa being the first of all therapies. This is a rudimentary attempt to understand how rasa, guna virya, and prabhav of these 10 medications may work to dissolve the disease of sushka arsha.